Left atrial thrombus: Rare and unusual presentation of Mycoplasma pneumoniae infection: A case Report - Sagar Lad; Pradeep Suryawanshi; Santosh Kait; Preeti Lad; Jalil Mujawar (Wolters Kluwer Medknow Publications, 2021)
Mycoplasma pneumoniae is a common organism responsible for pediatric community-acquired pneumonia. Extrapulmonary complications including thrombosis, although rare, are known to be associated with severe M. pneumoniae pneumonia. We report the case of left atrial thrombus extending into right inferior pulmonary vein in a child with severe M. pneumoniae probably due to transient Antiphospholipid Antibodies (aPL). Pneumonia and thrombus were completely resolved after the treatment with antimicrobial and anticoagulant therapy in 3 months. aPL are more common in M. pneumoniae infections; hence, routine screening will be helpful to quantify the incidence of aPL as well as to plan future risk assessment and management strategies.